GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA PENGGUNA KONTRASEPSI PIL KB DI PUSKESMAS DERMAYU KABUPATEN SELUMA - Mardiyansyah Bahar; Eka Nuradianty Anwar (LPPM Universitas Abdurrab, 2022)
Abstract Hormonal contraceptives are one of the modern types of contraceptives that contain the hormones estrogen and progesterone where the pill method is also widely used in birth control users, Side effects caused include abnormalities in glucose metabolism in the body which results in an increased risk of developing DM (Diabetes Mellitus). The purpose of this study was to determine the picture of blood glucose levels when in contraceptive users of birth control pills at the Dermayu Health Center, Seluma Regency. Method: This research was carried out on May 20-25, 2021 at the Clinical Chemistry Laboratory of the Harapan Bangsa Bengkulu Health Analyst Academy. The sampling technique uses purposive sampling, the sample taken is 30 mothers who use contraceptive birth control pills over 1 year at the Dermayu Health Center, Seluma Regency. This type of research is descriptive. Results and discussion: Blood sample results from 30 samples obtained 1 sample of low blood glucose levels (3.3%), 20 samples of normal levels (66.7%), 6 samples of high levels (20%) and 3 samples of very high levels (10%). Conclusion: It was concluded that the use of birth control pills does not have a significant negative impact so there is no need to worry about long-term use while maintaining a healthy lifestyle. Keywords: Glucose Levels, Birth Control Pill Contraceptives